2008
DOI: 10.1113/jphysiol.2008.160457
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of triadin 95 causes parallel changes in localized Ca2+ release events and global Ca2+ signals in skeletal muscle cells in culture

Abstract: The 95 kDa triadin (Trisk 95), an integral protein of the sarcoplasmic reticular membrane in skeletal muscle, interacts with both the ryanodine receptor (RyR) and calsequestrin. While its role in the regulation of calcium homeostasis has been extensively studied, data are not available on whether the overexpression or the interference with the expression of Trisk 95 would affect calcium sparks the localized events of calcium release (LCRE). In the present study LCRE and calcium transients were studied using la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…From these experiments and from those presented below (see Fig. 4), as well as from our earlier results [9] we concluded that the transfection with the empty vector does not affect the IP 3 pathway. To examine the effect of the inhibition of IP 3 Fig.…”
Section: Effect Of Trisk 32 Overexpression On the Function Of Ip 3 Resupporting
confidence: 47%
See 2 more Smart Citations
“…From these experiments and from those presented below (see Fig. 4), as well as from our earlier results [9] we concluded that the transfection with the empty vector does not affect the IP 3 pathway. To examine the effect of the inhibition of IP 3 Fig.…”
Section: Effect Of Trisk 32 Overexpression On the Function Of Ip 3 Resupporting
confidence: 47%
“…By measuring the amplitude and the integral of the thapsigargin-evoked Ca 2+ transients and finding no significant difference in either when comparing control and transfected cells, suggest that the overexpression of Trisk 32 does not affect the Ca 2+ content of the ER Ca 2+ store. The 95 kDa isoform of triadin is known to regulate Ca 2+ release via RyRs [9,24]. To exclude the possibility that such an interaction from Trisk 32 or an enhanced CICR was responsible for the increased Ca 2+ transients evoked by bradykinin or AVP, functional [Ca 2+ ] i measurements were performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although originally thought to be the link between RyR1 and DHPR (6 -8) and a key modulator of EC coupling (9 -11), it appears evident now that triadin acts primarily as a negative regulator of RyR1 activity (12)(13)(14)(15). Although the mechanism by which triadin regulate RyRs remains unclear, there is support for the hypothesis that triadin is involved in facilitating the cross-communication be-tween calsequestrin (CSQ) and the RyRs (16 -18).…”
mentioning
confidence: 85%
“…Overexpression studies using adenoviruses have shown that Trisk 95 is able to block the depolarization-induced calcium release, but in the same conditions, no effect was observed with Trisk 51 overexpression, and therefore no function could be attributed to this isoform (21). Triadin knockdown has also been realized using small interference RNA in cultured cells (22,23), and resulted in reduction of the depolarization-induced calcium release. In addition to various functional effects resulting from expression modification, the triadin isoforms have different localizations and partners, and whereas Trisk 95 and Trisk 51 are both located within the…”
mentioning
confidence: 99%